Global and Local Structural Changes of Cytochrome c and Lysozyme Characterized by a Multigroup Unfolding Process - Shiu, Ying-Jen (The Biophysical Society, 2008)
Equilibrium unfolding behaviors of cytochrome c and lysozyme induced by the presence of urea (0–10 M) as well as changes in temperature (295–363 K) or pH (1.8–7) are examined via small-angle x-ray scattering and spectroscopic techniques, including circular dichroism and optical absorption. Denaturant and temperature effects are incorporated into the free energy expression for a general multigroup unfolding process. Results indicate that there are at least four unfolding groups in the temperature-, urea-, or pH-induced unfolding of cytochrome c: two of these are related to the prosthetic heme group, and the other two correspond, respectively, to the unfolding of α-helices and global changes in protein morphology that are largely unaccounted for by the first two groups. In contrast, the unfolding of lysozyme approximately follows a simple one-group process. A modified mean-field Ising model is adopted for a coherent description of the unfolding behaviors observed. Thermodynamic parameters extracted from simple denaturing processes, on the basis of the Ising model, can closely predict unfolding behaviors of the proteins in compounded denaturing environments.